Asian economic cooperation in the new millennium : China's economic presence - Wiemer, Calla; Cao, Heping, 1957- (Advanced research in Asian economic studies, 2004)
This volume is the outgrowth of a conference held at Peking Universityin May 2002, jointly sponsored by the American Committee on AsianEconomic Studies, the Peking University School of Economics, and theChina Reform Forum. The contributors include leading scholars fromAsia as well as specialists on Asia from the US, Europe, andAustralia.